Pengaruh Kualitas SDM, Pemanfaatan Teknologi Informasi, SPI dan Penerapan SAP terhadap Kualitas Laporan Keuangan Pemerintah Kabupaten Lombok Barat - Muh. Hirzun, Muh. Hirzun; Astini, Yuli; Fauzi, Agus Khazin; Dony Hidayat (Indonesian Journal Publisher, 2024)
This study aims to determine the effect of human resource quality, utilization of information technology, internal control systems and application of government accounting standards on the quality of financial reports of regional apparatus organizations (OPD) in West Lombok Regency. This type of research is associative. The sampling technique used in this study is the purposive sampling technique. The research sample was 96 financial employees in 32 OPDs in West Lombok Regency. The analysis method used in this study is the multiple linear analysis method. The test results show that partially the quality of human resources, utilization of information technology and internal control systems do not have a significant effect on the quality of financial reports, while the variable of application of government accounting standards has a significant effect on the quality of financial reports of OPDs in West Lombok Regency. The influence of human resource quality variables, utilization of information technology, internal control systems and implementation of government accounting standards (independent variables) in contributing to the quality of financial reports (dependent variables) is 14% while the remaining 86% is the contribution of other variables not included in this study.